The natural and human-mediated expansion of a human-commensal lizard into the fringes of Southeast Asia - Benjamin R., Karin; Michael, Lough‑Stevens; Lin, Te‑En; Sean B., Reilly; Anthony J, Barley; Indraneil, Das; Djoko T., Iskandar; Evy, Arida; Todd R, Jackman; Jimmy A., McGuire; Aaron M., Bauer (BioMed Central, 2024)
Background Human‐commensal species often display deep ancestral genetic structure within their native range and founder‐effects and/or evidence of multiple introductions and admixture in newly established areas. We inves‐ tigated the phylogeography of Eutropis multifasciata, an abundant human‐commensal scincid lizard that occurs across Southeast Asia, to determine the extent of its native range and to assess the sources and signatures of human introduction outside of the native range. We sequenced over 350 samples of E. multifasciata for the mitochondrial ND2 gene and reanalyzed a previous RADseq population genetic dataset in a phylogenetic framework. Results Nuclear and mitochondrial trees are concordant and show that E. multifasciata has retained high lev‐ els of genetic structure across Southeast Asia despite being frequently moved by humans. Lineage boundaries in the native range roughly correspond to several major biogeographic barriers, including Wallace’s Line and the Isth‐ mus of Kra. Islands at the outer fringe of the range show evidence of founder‐effects and multiple introductions. Conclusions Most of enormous range of E. multifasciata across Southeast Asia is native and it only displays signs of human‐introduction or recent expansion along the eastern and northern fringe of its range. There were at least three events of human‐introductions to Taiwan and offshore islands, and several oceanic islands in eastern Indonesia show a similar pattern. In Myanmar and Hainan, there is a founder‐effect consistent with post‐warming expansion after the last glacial maxima or human introduction.